PERAN STRATEGIS PENDIDIKAN KELUARGA DALAM MEMBENTUK KARAKTER ANAK USIA DINI - Hubbil Khair (CV. ADIBA ASIHA AMIRA, 2025)
Character education in early childhood is the primary foundation for developing strong personality and morals. The family plays a strategic role as the primary educational institution, instilling moral, social, and spiritual values ​​from an early age. This study uses a qualitative approach with observation and documentation methods to describe the role of families in early childhood character education. The results indicate that key strategies that families can implement include role modeling, positive habits, supervision and communication, rewards and consequences, and providing a supportive environment. However, in practice, families face various challenges such as limited time, lack of knowledge about appropriate parenting styles, the influence of the media and the external environment, inconsistent parenting, and social and economic pressures. Therefore, character education in the family requires awareness, consistency, and the support of a conducive environment to shape a generation with character, responsibility, and readiness to face future social dynamics.